Management and Outcomes of Congenital Atrioventricular Block in Neonates: A 6-Year Experience at a Tunisian Tertiary Center - Aziza, Rim B.; Hajji, Sameh; Samaali, Khaoula; Chourou, Hajer; Ammar, Wafa B.; Aba, Neila B.; Neji, Khaled; Kacem, Samia (American Journal of Perinatology Reports, 2025)
Congenital atrioventricular block (CAVB) is a rare and serious condition often associated with maternal autoimmune diseases or congenital heart defects. This study aims to evaluate the clinical presentation, management, and outcomes of neonates diagnosed with CAVB.We conducted a retrospective study from January 2018 to December 2024, including eight neonates diagnosed with CAVB. Data on demographics, clinical features, treatment, and follow-up were analyzed.All cases were prenatally diagnosed between 20 and 25 weeks of gestation, with positive anti-SSA/SSB antibodies in five cases. Management included cesarean delivery, Holter ECG monitoring, and pacemaker implantation for four patients. One case resulted in intrauterine fetal death, and two patients died in the neonatal period. Survivors had successful pacemaker implantation with an average follow-up of 18 months.Early prenatal detection and timely management of CAVB are crucial. Pacemaker implantation significantly improves survival, though challenges such as resource limitations and the lack of long-term follow-up data remain. Future studies should address these gaps to optimize care for CAVB patients.
Keywords: prenatal diagnosis; congenital atrioventricular block; echocardiography; pacemaker